Polygenic hypercholesterolemia: examples of GWAS results and their replication in the Czech-Slavonic population - Hubáček, Jaroslav; Adámková, Věra; Lánská, Věra; Dlouhá, Dana (Physiological research, 2017)
Since 2007, the year of their first widespread use, genome-wide association studies (GWAS) have become the "gold standard" for the detection of causal genes and polymorphisms in all fields of human medicine. Cardiovascular disease (CVD), one of the major causes of morbidity and mortality, is no exception. The first GWAS focused on hypercholesterolemia and dyslipidemia as the major CVD determinants. GWAS confirm the importance of most of the previously identified genes (e.g. APOE, APOB, LDL-R) and recognize the importance of new genetic determinants (e.g. within the CILP2 or SORT1 gene clusters). Nevertheless, the results of GWAS still require confirmation by independent studies, as interethnic and interpopulation variability of SNP effects have been reported. We analyzed an association between eight variants within seven through GWAs detected loci and plasma lipid values in the Czech post-MONICA population sample (N=2,559). We confirmed an association (all P<0.01) between plasma LDL-cholesterol values and variants within the CILP2 (rs16996148), SORT1 (rs646776), APOB (rs693), APOE (rs4420638) and LDL-R (rs6511720) genes in both males (N=1,194) and females (N=1,368). In contrast, variants within the APOB (rs515135), PCSK9 (rs11206510) and HMGCoAR (rs12654264) genes did not significantly affect plasma lipid values in Czech males or females. Unweighted gene score values were linearly associated with LDL-cholesterol values both in males (P<0.0005) and females (P<0.00005). We confirmed the effects of some, but not all analyzed SNPs on LDL-cholesterol levels, reinforcing the necessity for replication studies of GWA-detected gene variants.
Keywords: dospělí; Female; hypercholesterolemie; Genome-Wide Association Study; LDL-cholesterol; Adult; Cholesterol, LDL; ženské pohlaví; jednonukleotidový polymorfismus; Slovakia; lidé; surveillance populace; Polymorphism, Single Nucleotide; Hypercholesterolemia; Male; Czech Republic; multifaktoriální dědičnost; Population Surveillance; celogenomová asociační studie; Multifactorial Inheritance; Česká republika; lidé středního věku; Slovenská republika; mužské pohlaví; Middle Aged; Humans